Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Foot Print Game di TK Negeri Pembina Pancur Batu T.A 2021/2022 - Ekayanti Tarigan; Servista Bukit (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this classroom action research is to improve the gross motor skills of children aged 5-6 years in Pembina State Kindergarten, Kec. Pancur Batu through foot print game. Foot print game activities are very beneficial for children's gross motor development. This classroom action research procedure uses the Kemmis and McTaggart model through four stages: planning, action and observation, reflection. Collecting data using interviews, observation, and documentation. This research was carried out in two cycles and each cycle was an improvement based on the results of reflections from the previous cycle. The results of this study indicate that the foot print game can improve the gross motor skills of group B children aged 5-6 years in Pembina State Kindergarten, Kec. Pancur Batu with a classical percentage in the initial cycle of 49.69% in the Poor category, the first cycle obtained a classical percentage of 60.31% in the Moderately Able category and in the second cycle the classical percentage was obtained by 73.43% in the Able category.